Teachers’ misconception concerning valence and valency in chemistry - Raghubir Singh Sindhu (ICASE, 2021)
A study on the misconceptions developed or held by teachers related to the two terms valence and valency was undertaken. A total of 48 teachers (26 males and 22 females) teaching the chemistry component of science subject to 14- to 16-year-old students, in 48 schools affiliated to one district, were randomly selected for the study by taking one teacher from each school. One session was devoted for administering the questionnaire among the teachers and second session (with a gap of one day) was for addressing the teacher’s misconceptions. From the analysis of the responses, it was found that the two terms although they have the same meaning were misconceived as having different meanings. Due to this a misleading relationship between the two terms was discovered. Even the highest numerical value of valence was misconceived. The possible reasons for these misconceptions were identified. A simple, brief, and precise description of the concepts was presented to remove the misconceptions of the teachers.